Non-vascular interventional radiology of the abdomen - Arellano, Ronald S.; SpringerLink (Online service). (New York Springer, 2011)
This book is designed to provide a foundation for physicians-in-training and a quick guide to further enhance the skills set of practicing interventionalists. It is a concise reference manual covering the major aspects of clinical scenarios, procedures, and techniques. "Non-Vascular Interventional Radiology of the Abdomen" expertly addresses the planning and execution of commonly encountered procedures, including organ specific biopsies, abscess drainage, urinary interventions, gastrostomy, gastrojejunostomy, and biliary interventions.
Patient evaluation and preparation -- Image-guided percutaneous biopsy -- Percutaneous abscess drainage -- Percutaneous urinary interventions -- Percutaneous gastrostomy and gastrojejunostomy -- Biliary Interventions.
Electronic reproduction.
Keywords: Medical radiology; Abdomen -- Interventional radiology; Electronic books